MEKANISME MATA UANG MODERN DALAM ISLAM - Azwar Hamid (Institut Agama Islam Negeri Padngsidimpuan, 2017)
Money is currency exchange to get human needs such as a certain object. It becomes the main facility in doing transaction between two people or more. In addition, in Islamic view money is a currency as a tool that only can be made to buy something not as a commodity which means that it cannot be bought by money itself. So, Islamic Economy defines that money cannot be made as a commodity as the others in general economy.